ANALYSIS OF THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK-EMKM) IN THE PREPARATION OF FINANCIAL STATEMENTS IN BUSINESS MABEL LIA PERABOT - Ayu Sufi Lestari; Vidya Fathimah (SEAN Institute, 2023)
The purpose of this research is how is the analysis of the application financial accounting standads for micro, small and medium entities (Sak-emkm) in the preparation of financial statemens for the mabel lia furniture business. The research was conducted using a qualitative method that leads to the description and application of SAK-EMKM based financial records by conducting interviews and talking financial reports to be processed to comply with SAK-EMKM. The results of the study show is Mabel Lia Perabot business does not apply SAK-EMKM in preparing its financial statements, the owner considers that the recording is clear and effective, constraints faced by these UMKM lack of owner knowledge about SAK-EMKM, there is no professional accounting staff, and owners do not understand the importance of recording and preparing reports.